직장 내 괴롭힘·성희롱 ‘업무’요건의 쟁점 및 개선방안 - 이재현(Lee, Jaehyun) (이화젠더법학, 2024)
직장 내 괴롭힘･성희롱 사건은 여러 당사자가 관계되거나 다수 행위가 결합하는 등 복잡한양상으로 진행되곤 한다. 최근, 인사위원회나 징계위원회에서 ‘업무’ 범위의 해석이 쟁점이 되는경우가 있다. 예를 들어, 근로시간이나 사업장에서 거리가 있는 행위의 경우, 이를 직장 내괴롭힘･성희롱으로 인정할 수 있을지가 문제 된다. 행위자는 행위의 잘못은 인정하면서도, 업무관련성이 없어 법에서 금지하는 직장 내 괴롭힘･성희롱은 아니고, 사용자가 징계할 수 없다고주장할 수 있다. 실무적으로 업무 관련성을 폭넓게 인정하는 경향이 나타나지만, 법 논리적근거는 충분히 정립되지 못한 상황이다. 이에 따라 직장 내 괴롭힘･성희롱의 '업무' 요건을명확하게 정리하고 적용하려는 노력이 필요하다. 본 연구는 이러한 문제의식을 바탕으로 직장내 괴롭힘･성희롱의 업무 요건에 관한 쟁점을 살펴보고, 입법･정책적 개선방안을 제시했다. 직장내 괴롭힘은 ‘일탈행위’를 포함하여 범위를 명확히 하는 안, 고용노동부 매뉴얼의 업무 관련성내용을 수정하는 안, ‘일탈행위’와 ‘업무상 적정범위’에 관한 판단기준을 새롭게 설정하는 안을제시했다. 직장 내 성희롱은 ‘지위 이용’ 요건을 삭제하는 안, 업무 관련성의 범위와 내용을법령에 구체적으로 명시하는 안, 업무 관련성 판단기준을 고용노동부 매뉴얼에 삽입하는 안을고려해 볼 수 있다. 개선 노력을 통해 법 제도로서 직장 내 괴롭힘･성희롱 금지 제도가 더욱성숙해지고, 많은 근로자가 안전하고 존중받는 일터에서 일할 수 있게 되기를 기대한다. Harassment and sexual harassment at workplaces often involve multiple stakeholders within the workplace and occur in complex manners. Recently, there has been a growing debate in disciplinary committees and personnel review boards on how to interpret the scope of “work.”. For example, if a perpetrator’s behavior occurs outside of working hours or away from the workplace, it becomes contentious whether such actions can be recognized as workplace harassment or sexual harassment in the workplace. While perpetrators may acknowledge their behavior was wrongful, they could argue that it lacks work-relatedness, claiming it does not constitute prohibited harassment or sexual harassment under the law, and therefore cannot be subject to employer sanctions or disciplinary actions. In practice, there is a tendency to broadly interpret work-relatedness, but the legal and logical basis for such interpretations remains underdeveloped. Accordingly, efforts are needed to more clearly redefine and apply the ‘work-relatedness’ requirement for workplace harassment and sexual harassment at work. Recognizing this need, this study examines key issues surrounding the work-relatedness requirement in cases of workplace harassment and sexual harassment and suggests legislative and policy improvements. For workplace harassment in general, the study proposes including “deviant behavior”, modifying references to work-relatedness in the Ministry of Employment and Labor’s guidelines, and establishing new criteria for determining “deviant behavior” and “the appropriate scope of work”. For workplace sexual harassment, this study proposes removing the requirement for “abuse of authority”, specifying the scope and content of work-relatedness in legal provisions, and including criteria for determining work-relatedness in the Ministry of Employment and Labor’s manual. Through these improvements, the legal framework for addressing workplace harassment and sexual harassment is expected to mature further, ensuring safer and more respectful work environment for many employees. KCI Citation Count: 0